Mineral Elements and Antioxidant Activity of Three Locally Edible and Medicinal Plants in Iran - Ali Ebrahimzadeh, Mohammad; Mohammad Nabavi, Seyed; Fazel Nabavi, Seyed; Eslami, Shahram; Reza Bekhradnia, Ahmad (Asian Journal of Chemistry, 2010)
Certain inorganic trace elements play an important role in biochemical process in cell. In the present study, the elemental composition (Zn, Fe, Cu, Mn, Ni and Cr) in three locally edible traditional medicinal plants (Diospyros lotus fruit, Froriepia subpinnata and Eryngium caucasicum leaves) widely used in some disorders has been studied using atomic absorption spectroscopy. In addition, total antioxidant capacity and their total phenol and flavonoid contents were investigated by various assay systems. Iron, zinc and manganese were ranked the highest amounts in three plants. F. subpinnata and E. caucasicum leaves are better sources for minerals than D. lotus fruit. Extracts also showed good antioxidant activity in tested models. Specially, F. sabpinnata aqueous extract with the amount of phenol and flavonoids showed high activity.